Perancangan Translator Bahasa Alami ke dalam Format SQL (Structured Query Language) - Kuspriyanto Kuspriyanto; Herry Sujani; Hary Tjahjono; Shofyan Kusuma (Teknoin, 2005)
In order to able to use SQL (Structured Query Language) properly, users should understand structure of SQL. In this research, a prototype of translator from natural language to SQL format is developed to facilitate novice users to get information from a database. Using three databases, testing results indicate that the translator gives accuracy  of 86%. Keywords: natural language translator, SQL